PENGEMBANGAN BUKU PENGAYAAN TEKS DESKRIPTIF PERISTIWA BUDAYA BERBASIS KONTEKSTUAL BAGI SISWA KELAS VII DI KABUPATEN KENDAL - dewangga, arta permana (Piwulang : Jurnal Pendidikan Bahasa Jawa, 2020)
The objectives of this study were (1) to describe the needs analysis of students, teachers, and the community for textbooks enriching contextual cultural events desciption texts for class VII students, (2) to compile a prototype textbook enrichment description of contextual-based cultural events for students of class VII, and (3) describe the results of expert tests from the prototype enrichment text book description of contextual-based cultural events for students of class VII. This study used research and development (R & D) method with the stages of research carried out, which include, (1) potential and problems, (2) data collection, (3) product design, (4) product validation, and (5) product revisions. The data contained in this study are learning process data and the availability of enrichment books in schools, needs analysis, cultural events from the speakers, and data from validation tests. The subjects of this study were teachers, students, the community and resource persons, as well as material and media experts. Data collection techniques carried out by observation, interviews, questionnaires, and expert test assessment sheets. Analysis of the data used in this study is qualitative descriptive. The research produced was a descriptive text enrichment book on Javanese-language cultural events containing eight cultural events in Kendal District. The enrichment books produced have been validated by material experts and media experts. The results of the validation test are enrichment text descriptions of cultural events that are appropriate and suitable to be used as enrichment books and Javanese language learning media for seventh grade students in Kendal Regency. Keywords: Enrichment Books, Cultural Event, Contextual.